The Methods to Guide Students to Experience the Process of Knowledge Generation - Zhang, Aijuan (Journal of Theory and Practice of Contemporary Education, 2023)
In teaching, students should be guided to constantly "clean the sand", constantly analyze knowledge layer by layer from the outside to the inside, expose the process of thinking development, experience the process of knowledge generation, and finally "harvest gold" - to construct their own mathematical knowledge. Pay attention to experience and expose the formation process of concept; Camera induction, the exploration process of exposure rules; Encourage debate and expose the improvement process of conclusions; Try to make mistakes and expose the correction process of mistakes. Only by allowing students to experience mathematics and expose the process of thinking development can they really "Touch Math".